Pengaruh Manajemen Sumber Daya Manusia Untuk Meningkatkan Mutu Pendidikan Di Sekolah Dasar Negeri Ii Bakalanpule - Kuswanto Kuswanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
In order to improve the quality of education, the thing that needs to be considered is about Human Resource Management because without the support of good human resources, an organization or educational institution will not be able to progress and develop. Therefore, every organization or educational institution that wants to progress and develop must pay attention to human resources and manage them properly, in order to create quality education. This study aims to determine whether human resource management is very influential in improving the quality of education at the State Elementary School II Bakalanpule. The research method uses field research with a qualitative descriptive approach which aims to obtain information about the existing conditions and is designed to collect information about real, ongoing conditions. The results of this study indicate that human resource management has a very good influence on improving the quality of education at the State Elementary School II Bakalanpule where the principal assigns all teachers to participate in several activities and programs to support the ability and competence of teachers to continue to improve and develop, including is participating in seminars and training activities. Programs and activities to increase entrepreneurial, supervisory, managerial and entrepreneurship skills and are supported by educational staff who implement a good quality culture so that in terms of improving the quality of education it is very effective.